Status gizi pasien bedah mayor preoperasi berpengaruh terhadap penyembuhan luka dan lama rawat inap pascaoperasi di RSUP Dr Sardjito Yogyakarta - Susetyowati Susetyowati; Maya Ija; Akhmad Makhmudi (Jurnal Gizi Klinik Indonesia, 2010)
Background: Severe malnutrition affects morbidity due to disrupted wound healing and decreased endurance against infection. There are some factors that cause malnutrition in surgical patients. Two major factors are lack of food intake and process of inflammation that cause increase of catabolism and decrease of anabolism. The condition can be identified from the decrease of albumin serum and muscle hypothrophy.Objective: The study aimed to identify impact of nutrition status of preoperative major surgical patients based on Nutritional Risk Index (NRI) indicator to wound healing and post operative length of stay.Method: The study was observational with prospective cohort study design. Nutrition screening was undertaken to the group that met inclusion criteria at the preliminary process of hospitalization using NRI indicator to identify nutrition status of surgical patients. Next, the group was split into two, one with undernourished nutrition status and the other with good nutrition status. Assessment of nutrition status of patients was based on NRI obtained from level of serum albumin and current and usual weight ratio within the last 6 months. Weight assessment was made during early hospitalization or weight within the last 6 months.Result: The result of the study showed there was signifiant association between nutrition status and wound healing and post operative length of stay (p<0.05). The result of logistic regression test showed there was impact of nutrition status to wound healing and post operation length of stay. Patients with undernourished nutrition status based on NRI contributed 4.8 times greater for the prevalence of poor wound healing than those with good nutrition status (95%CI: 1.179-19.880). Patients with undernourished nutrition status based on NRI contributed 5.5 times greater for extended length of stay > 7 days than those with good nutrition status (95% CI:4.701-50.914).Conclusion: There was impact of nutrition status of preoperative major surgical patients based on NRI indicator to wound healing and post operative length of stay.